Effectiveness of the Educational Program on Nurses’ Knowledge concerning Hyperosmolar Hyperglycemic State - Baqer Raad Farhood,; Musaab Majid Abdulwahhab, (AlQalam Journal of Medical and Applied Sciences, 2024)
Hyperosmolar Hyperglycemic State (HHS) is one of the acute diabetic complications that commonly seen with type 2 diabetes mellitus (T2DM). This represents a critical case necessitating prompt and efficient intervention to prevent potential severe complications. Nursing plays a crucial role in the care of these patients at the critical care settings. Specifically, the project aims to investigate whether nurses' HHS knowledge can be enhanced by educational programs. Quasi-experimental design was used to investigate the effect of the educational program on nurses’ knowledge about HHS at Al-Diwaniyah Teaching Hospital in three unites: Cardiac Care Unites (CCU), respiratory care unit (RCU) and emergency room (ER). A non-probability (purposive) sample was chosen from nurses who works in these three unites, the study group consisted of 35 nurses, while the control group comprised 41 nurses. A statistical package for social science (SPSS) program, version 26 was used for descriptive and inferential statistics. By comparing the nurses’ knowledge about HHS between the test before (6.4286± 1.35659) and after the program (8.2000± 1.10613), there is a significant difference in nurses’ knowledge after the program in the study group, but as for the control group, there is no difference. By comparing the nurses' knowledge regarding nursing care of HHS between the test before (14.0286± 2.05062) and after the program (16.6286± 1.41600), there is a significant increase in nurses' knowledge about nursing care of HHS after the program in the study group. The finding of study show that the educational program was effective to enhance nurses’ knowledge about HHS. تعد حالة فرط الأسمولية السكرية واحدة من المضاعفات السكرية الحادة الشائعة التي تُرى مع مرض السكري من النوع الثاني. تمثل هذه الحالة حالة حرجة تتطلب تداخلاً سريعًا وفعالًا لمنع المضاعفات الشديدة المحتملة. يلعب التمريض دورًا حاسمًا في رعاية هؤلاء المرضى في أماكن الرعاية الحرجة. على وجه التحديد، يهدف المشروع البحثي إلى التحقيق فيما إذا كان من الممكن تعزيز معارف الممرضين حول حالة فرط الأسمولية السكرية من خلال البرنامج التعليمي. تم استخدام التصميم شبه التجريبي للتحقيق في تأثير البرنامج التعليمي على معارفة الممرضين بحالة فرط الأسمولية السكري في مستشفى الديوانية التعليمي في ثلاث وحدات: وحدات العناية القلبية و وحدة العناية التنفسية وغرفة الطوارئ. تم اختيار عينة غير عشوائية (غرضية) من الممرضين الذين يعملون في هذه الوحدات الثلاث، وتألفت مجموعة الدراسة من 35 ممرض، بينما ضمت المجموعة الضابطة 41 ممرض. تم استخدام برنامج الحزمة الإحصائية للعلوم الاجتماعية (SPSS)، الإصدار 26 للإحصاء الوصفي والاستدلالي. من خلال مقارنة معارف الممرضين حول فرط الأسمولية السكرية بين الاختبار قبل البرنامج (6.4286 ± 1.35659) وبعد البرنامج (8.2000 ± 1.10613)، حيث يوجد فرق كبير في معارف الممرضين بعد البرنامج في مجموعة الدراسة، أما بالنسبة للمجموعة الضابطة، فلا يوجد فرق. من خلال مقارنة معارف الممرضين فيما يتعلق بالرعاية التمريضية لفرط الأسمولية السكرية بين الاختبار قبل البرنامج (14.0286 ± 2.05062) وبعد البرنامج (16.6286 ± 1.41600)، وجدت زيادة كبيرة في معارف الممرضين حول الرعاية التمريضية لفرط الأسمولية السكرية بعد البرنامج في مجموعة الدراسة. تظهر نتائج الدراسة أن البرنامج التعليمي كان فعالاً في تعزيز معارف الممرضين حول فرط الأسمولية السكرية